Atuação do psicólogo na educação escolar: uma análise de práticas que visam atender à perspectiva inclusiva - Martins, Tânia Gonçalves (2008)
The social inclusion process is becoming each time more present and has provoked a series of restructures in all the environments where it is inscribed. To attend to this paradigm, the Minas Gerais Education State Secretariat has implemented, in 2006, the project Special Schools: a new time, mobilizing the professionals of special schools to restructure the services and revise their practices to transform these institutions in Support Centers for the Inclusive Education instituting a new service model. The changes by which the Belo Horizonte special education public schools have passed through to act in this model of Support Centers were adopted as an initial landmark of the present research. Considering that these institutions count on the services of psychologists and that these professionals are involved in this transformation process, the aim of this work is to identify the functions attributed to these professionals at the institutions Politic Pedagogic Projects (PPPs) and the functions that they attribute to themselves, trying to comprehend how they have been restructuring their practices to attend to the inclusive perspective and to act at the special schools reconfigured as Support Centers. The methodology was developed in two stages: 1) identification of the psychologists functions at the seven special education public institutions of Belo Horizonte which attend students with mental retardation, by means of a documental analysis of the schools PPPs elaborated to restructure the services according to the new Support Center model; 2) identification and analysis of the functions that the psychologists (total of 14 professionals) declared to carry out to attend to the inclusive perspective, by means of semi-structured individual interviews. The documental analysis showed that the psychologists activities differ in the manner that the task is realized individually or in group and in the concept of service underlying the task. This result permitted the creation of categories of analysis which served as reference to the analysis realized at the second part of the research. The interview stage revealed the functions that the psychologists were developing at the institutions and which of these functions attended to the inclusive perspective. It can be concluded that the model of the special school as a Support Center for common schools is still not a reference for these professionals since it was verified a variation in the perspectives of service done by the psychologists some functions were developed with activities that attended the special education demands in the traditional molds, and others were gaining inclusive outlines by reason of the service they were related to or, in rare exceptions, for a effective change of service concept by the professionals